Polymorphism and association of growth hormone gene with growth traits in Sirohi and Barbari breeds of goat - Singh, Praduman Pal (Vet World, 2015)
AIM: The aim was to study the polymorphism of exon 2 and exon 3 of growth hormone (GH) gene, to test the polymorphic variants for Hardy–Weinberg equilibrium and to investigate association of these polymorphisms with chest girth and paunch girth in Sirohi and Barbari breeds of goat. MATERIALS AND METHODS: A total of 80 kids involving forty each of Sirohi and Barbari breeds of goat were included in the study. A good quality genomic DNA isolated from the whole blood using standard protocol were used for polymerase chain reaction (PCR) amplification and products obtained on restriction digestion of amplicon with enzyme HaeIII were separated on 2% agarose gel, and documented in a gel doc system. The chest girth and paunch girth of kids at birth and weekly intervals up to 4 weeks of age and subsequently at 2 months, 3 months and 6 months of age were recorded. Allele frequency and genotype distribution of polymorphism were tested for Hardy–Weinberg equilibrium by program me Genepop package. Association between different genetic variants on chest girth and paunch girth were analyzed by least squares analysis employing suitable statistical model. RESULTS: The PCR product of genomic DNA isolated from kids of Sirohi and Barbari breeds of goat on digestion with the restriction enzyme HaeIII revealed two genotypic variants viz., AB and BB. None of the two breeds was in Hardy–Weinberg equilibrium for these variants. The least squares analysis of variance revealed non-significant effect of GH genotype and breed × genotype interaction on chest girth and paunch girth from birth to 180 days of age. The effect of breed was highly significant (p<0.01) at all ages. CONCLUSION: The present study showed that both the breeds were polymorphic at the exon 2 and exon 3 loci of GH gene under study with respect to HaeIII restriction endonuclease. None of the breeds was in Hardy–Weinberg equilibrium for this region of GH gene. In the present study, no significant association between GH genotype and chest girth and paunch girth could be established but comparatively higher chest girth and paunch girth were observed for AB genotype across the breeds.